2013
DOI: 10.1016/j.matbio.2013.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and biophysical changes underlie the mechanisms of basement membrane disruptions in a mouse model of dystroglycanopathy

Abstract: Mutations in glycosyltransferases, such as protein O-mannose N-acetylglucosaminyltransferase 1 (POMGnT1), causes disruptions of basement membranes (BMs) that results in neuronal ectopias and muscular dystrophy. While the mutations diminish dystroglycan-mediated cell-ECM interactions, the cause and mechanism of BM disruptions remain unclear. In this study, we established an in vitro model to measure BM assembly on the surface of neural stem cells. Compared to control cells, the rate of BM assembly on POMGnT1 kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 73 publications
2
11
0
Order By: Relevance
“…Our result – that endoderm-free patient embryoid bodies show diminished laminin accumulation – corroborates evidence that αDG-deficient cells have reduced ECM-binding kinetics that might render basement membranes susceptible to mechanically-induced deformation [21, 52]. Crucially, we found that embryoid bodies undergo minimal volumetric growth.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our result – that endoderm-free patient embryoid bodies show diminished laminin accumulation – corroborates evidence that αDG-deficient cells have reduced ECM-binding kinetics that might render basement membranes susceptible to mechanically-induced deformation [21, 52]. Crucially, we found that embryoid bodies undergo minimal volumetric growth.…”
Section: Discussionsupporting
confidence: 88%
“…Knockout of dystroglycan in mouse embryonic stem cells and neural stem cells has been reported to reduce laminin polymerization at the cell surface, which is a prerequisite for basal lamina formation [21, 52]. Because we observed thinner basal lamina in dystroglycanopathy patient embryoid bodies, we next investigated whether this phenotype might be linked to a reduced ability to polymerize laminin.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Mechanically weakened BMs explain the frequent breaks of the ILM and pial BMs that are characteristic for these mice ( Fig. 2A-D) [80,85]. BM ruptures in brain and retina are found in mice and fish with mutations of almost all major BM proteins, including perlecan [28], laminins [30,31,34,35,37,86] and collagen IV [32,36,87].…”
Section: Biomechanical Properties Of Bmsmentioning
confidence: 99%
“…BM is a dynamic structure whose morphology and composition change in response to development, tissue types, aging, disease, and regeneration [37,38]. We previously reported that de novo BM formation is feasible when the epithelium and mesenchyme of SMGs were cultured in an environment composed of appropriate biomaterials [39], thus proving that the regulation of BM formation and activity is fundamental to promoting epithelial morphogenesis if the developmental scheme is to be recapitulated.…”
Section: Discussionmentioning
confidence: 99%